40 UMP undergrads volunteer for Singgah Sahur@KL programme - UMP, PNC (2019)
Universiti Malaysia Pahang’s (UMP) MyGift squad, comprising 40 undergraduates, recently took to the streets and participated in the renowned Singgah Sahur programme in the capital city of Kuala Lumpur on May 14, 2019.